19F NMR spectroscopy as a tool to detect rotations in fluorine substituted phenyl compounds. Issue 48 (27th November 2020) - Sun, Mingming; Chen, Wuhong; Zhang, Tao; Liu, Zhenjun; Wei, Junchao; Xi, Ning
Abstract: Atropisomerism becomes a popular structural feature in modern drug discovery. Using N -phenyl γ-lactam and phenyl-pyrazolone scaffolds, we showed that distinct 19 F NMR peaks were present in atropisomers and dual signals emerged for covalently identical fluorine nuclei in hindered rotamers. Factors affecting 19 F NMR chemical shifts in these molecules were discussed. We demonstrated that 19 F NMR spectroscopy can be used to differentiate and detect atropisomers and rotamers in conformationally restricted molecules. Graphical abstract: Image 1 Highlights: 19 F NMR signals are sensitive to chemical environments and can be used to monitor rotamers and atropisomers. Rotational barrier thresholds estimated by theoretical calculations correlate with 19 F chemical shift differentiation. 19 F NMR shift differences are useful parameters to detect spatially remote structural variations in molecules.